Analysis of The Influence of Monetary Variables and Foreign Direct Investment (FDI) on Indonesia's GDP From Q1 2014 to Q4 2023 - Astried Vanessa Akhzani; Tyas Danarti Hascaryani (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study focuses on understanding how monetary variables and Foreign Direct Investment (FDI) affect Indonesia's economic growth in the 2014 Q1-2023 Q4 timeframe. There is a research gap in examining the impact of M2, interest rates, exchange rates, inflation, and FDI on GDP in both the short and long term. This study uses a VAR / VECM model approach that will examine the relationship between these variables. The results of this study are M2 has no effect on GDP, interest rates and inflation have a negative impact on GDP. FDI and exchange rate have a positive impact on GDP. Thus, it is necessary to have an effective combination of monetary policy so that an increase in foreign direct investment flows can encourage more sustainable economic growth in Indonesia.